Silicon Electrodeposition for Microelectronics and Distributed Energy: A Mini-Review - Andrey Suzdaltsev (Electrochem, 2022)
Due to its prevalence in nature and its particular properties, silicon is one of the most popular materials in various industries. Currently, metallurgical silicon is obtained by carbothermal reduction of quartz, which is then subjected to hydrochlorination and multiple chlorination in order to obtain solar silicon. This mini-review provides a brief analysis of alternative methods for obtaining silicon by electrolysis of molten salts. The review covers factors determining the choice of composition of molten salts, typical silicon precipitates obtained by electrolysis of molten salts, assessment of the possibility of using electrolytic silicon in microelectronics, representative test results for the use of electrolytic silicon in the composition of lithium-ion current sources, and representative test results for the use of electrolytic silicon for solar energy conversion. This paper concludes by noting the tasks that need to be solved for the practical implementation of methods for the electrolytic production of silicon, for the development of new devices and materials for energy distribution and microelectronic application.